2018
DOI: 10.1016/j.ijscr.2017.10.068
|View full text |Cite
|
Sign up to set email alerts
|

A case report: Primary hydatid cyst of uterus

Abstract: HighlightsHydatid cyst in uterus is very rare.Especially in endemic area for this parasite, one of differential diagnoses of pelvic cyst must be echinococcosis.We here report a case of primary uterus hydatid cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Although, Tas et al (13), suspected an ovarian neoplasm in a 44-year-old menopausal patient with complaints of abdominal distention, they encountered primary ovary and omental CE during surgery. A case from Iran, primary uterus hydatid cyst removed from uterine on left ovary and fallopian tub of 46 years old women (14). In a six-year retrospective study of 18 patients treated surgically, localizations of CE were found in two tuba, one colon, omentum and uterus (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although, Tas et al (13), suspected an ovarian neoplasm in a 44-year-old menopausal patient with complaints of abdominal distention, they encountered primary ovary and omental CE during surgery. A case from Iran, primary uterus hydatid cyst removed from uterine on left ovary and fallopian tub of 46 years old women (14). In a six-year retrospective study of 18 patients treated surgically, localizations of CE were found in two tuba, one colon, omentum and uterus (15).…”
Section: Discussionmentioning
confidence: 99%
“…Human lungs were the second most common organ of involvement in adults, after the liver (Wilson, 1991). Hydatidosis of organs outside of liver or lung were unusual as CNS (Mazyad et al, 1999), heart, kidney, bone and ocular (Gogus et al, 2003), brain (Farahmand et al, 2010), ovary causing ovarian neoplasm (Sharma et al, 2012), pancreas (Akbulut et al, 2014), pelvic (Bhatnagar et al, 2017), breast (Temiz et al, 2017, uterus (Kakaei et al, 2017), foot (Ewnte, 2020), or even anal fossa (Abdalla et al, 2020). However, lungs were the most common site of involvement in children (Polat et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hydatid disease is a parasitic infection mostly caused by larvae of the Echinococcus granulosus [1,2]. It is common in sheep-raising countries [3] including the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…It is common in sheep-raising countries [3] including the Middle East. The disease is endemic in Iran, with most cases reported from north western region [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation